Peningkatan Pengetahuan Kebencanaan Masyarakat Pangandaran Dalam Mewujudkan Masyarakat Tahan Bencana - Priyo Subekti; Atwar Bajari; Dadang Sugiana; Hanny Hafiar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Pangandaran is an environmentally-based tourism destination that is quite popular in Indonesia, but Pangandaran has a high potential for disaster. Pangandaran is ranked 16th among all districts in Indonesia in terms of disaster potential. Therefore, a program is needed to increase community resilience, community adaptability to disasters, so that people are able to act quickly and precisely when disasters occur and communities are resistant to post-disaster effects. The methods used in this service include lectures, discussions and disaster simulations. With this service activity, it is hoped that the community can: 1) understand and know how to behave when a disaster occurs to reduce disaster risk, around their place of residence; 2) the community knows how and where to look for information on disaster which includes disaster techniques and management; 3) improve the physical and mental preparedness of the community when a disaster occurs; 4) provide an understanding to the community of the importance of preserving the environment in order to avoid disasters.